Fragmentation and Strategic Market-Making - Daures-Lescourret, Laurence; Moinas, Sophie (Journal of Financial and Quantitative Analysis, 2023)
Abstract How does trading in one venue affect the quoting strategies of market makers in other venues? We develop a two-venue imperfect competition model in which market makers face quadratic costs when absorbing shocks. Nonconstant marginal costs imply that absorbing a shock in one venue simultaneously changes marginal costs in all other venues. Moreover, market makers strategically choose which shock(s) to absorb. These two forces may intensify competition, leading to enhanced liquidity. Using Euronext proprietary data, we track individual best bid and ask quotes of intermediaries in each venue. We uncover evidence of strategic cross-venue market-making behavior which is uniquely predicted by our model.